Adsorption site, orientation and alignment of NO adsorbed on Au(100) using 3D-velocity map imaging, X-ray photoelectron spectroscopy and density functional theory. Issue 21 (16th May 2019) - Abujarada, Saada; Walton, Alex S.; Thomas, Andrew G.; Chohan, Urslaan K.; Koehler, Sven P. K.
Abstract : Molecular surface geometry of adsorbents by triangulation using 3D-velocity map imaging. Abstract : Nitric oxide adsorption on a Au(100) single crystal has been investigated to identify the type of adsorption, the adsorption site, and the orientation and alignment of the adsorbed NO relative to the surface. This was done using a combination of 3D-surface velocity map imaging, near-ambient pressure X-ray photoelectron spectroscopy, and density functional theory. NO was observed to be molecularly adsorbed on gold at ∼200 K. Very narrow angular distributions and cold rotational distributions of photodesorbed NO indicate that NO adsorbs on high-symmetry sites on the Au crystal, with the N–O bond axis close to the surface normal. Our density functional theory calculations show that NO preferentially adsorbs on the symmetric bridge (2f) site, which ensures efficient overlap of the NO π* orbital with the orbitals on the two neighbouring Au atoms, and with the N–O bond axis aligned along the surface normal, in agreement with our conclusions from the rotational state distributions. The combination of XPS, which reveals the orientation of NO on gold, with 3D-surface velocity map imaging and density functional theory thus allowed us to determine the adsorption site, orientation and alignment of nitric oxide adsorbed on Au(100).